Correlation between vigour tests and field emergence in cotton - P.Y. SHINDE; MALAVIKA DADLANI (Seed Research, 2026)
Considering that cotton hybrids are grown in a wide range of agro-ecological conditions, both rainfed and irrigated, it is important that the hybrid seeds should not only meet the minimum standards of germination, but exhibit high planting value (vigour) to ensure a successful field emergence and stand establishment. This can be achieved by providing high vigour seeds. Vigour assessment studies conducted in 21 commercial seed lots of hybrids and varieties of cotton showed significant differences in the lots for different physical, physiological and performance based vigour tests. The speed of germination, 100-seed weight and electrical conductance of seed leachates were found to be very good indicators of the planting value of seed lots. The germination in sand medium and brick-gravel test showed a positive correlation with field emergence in six months stored seeds.